Comparing King, Gentoo and Royal Penguin Responses to Pedestrian Visitation - Holmes, ND (2007)
For wildlife managers, determining inter-species differences in the behavioral responses of seabirds to visitation can allow greater efficacy of visitor guidelines. Two key management outcomes for such information include 1) tailoring visitor guidelines to protect the most sensitive species and 2) improving self-regulation during visits by identifying behaviors likely to indicate a change in the natural activity of visited species. On subantarctic Macquarie Island, Australia, I collected the behavioral responses of guarding king (Aptenodytes patagonicus), gentoo (Pygoscelis papua), and royal (Eudyptes schlegeli) penguins before, during, and after exposure to a standardized pedestrian visit, to compare species' behavioral responses to visitation. Gentoo penguins appeared more sensitive than royal or king penguins, exhibiting altered behavior for 5 minutes after the stimulus was removed; this pattern was not evident in kings or royals. Response behaviors useful for visitors to assess their impact on penguins include vigilance (repeated rapid head turning) in all 3 species, agonism in king and royal penguins (reaching and striking at conspecifics), and low threat-display (bill pointing) in gentoo penguins. This study is valuable for wildlife managers as it provides practical information in the application of on-ground visitor guidelines.